1990
DOI: 10.1002/jor.1100080107
|View full text |Cite
|
Sign up to set email alerts
|

An in vitro study of anterior cruciate ligament strain induced by quadriceps and hamstrings forces

Abstract: Strain in the anteromedial fibers of the anterior cruciate ligament [ACL(am)] was studied in six cadaver knees. ACL(am) strain was measured in five knees during the application of isometric quadriceps forces alone and simultaneously applied isometric quadriceps and hamstrings forces at 10 degrees increments from 0 degrees to 90 degrees of knee flexion. ACL(am) strain during muscle loading was measured with respect to the ACL(am) strain measured with the knee in its resting position (neutral or near neutral pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
93
1
6

Year Published

1991
1991
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 231 publications
(109 citation statements)
references
References 21 publications
9
93
1
6
Order By: Relevance
“…Durselen et al [7] reported that at 140 N quadriceps load, the ACL strain (2.5%) was at its maximum at about 25°flexion. Draganich and Vahey [8] also reported a similar observation. All of the above observations are under static conditions.…”
Section: Discussionsupporting
confidence: 53%
“…Durselen et al [7] reported that at 140 N quadriceps load, the ACL strain (2.5%) was at its maximum at about 25°flexion. Draganich and Vahey [8] also reported a similar observation. All of the above observations are under static conditions.…”
Section: Discussionsupporting
confidence: 53%
“…Consequently, prediction of the antagonist moment should take into consideration the effects of muscle length on the antagonist EMG and moment capacity of the hamstrings. Furthermore, previous studies have reported that the hamstring antagonist function is particularly important for knee joint stability at some angles (towards knee extension) compared to other parts of the movement (Draganich and Vahey 1990;Hirokawa et al 1992;More et al 1993;Solomonow et al 1987).…”
Section: Discussionmentioning
confidence: 98%
“…There are several factors responsible for these observations. Previous studies have indicated that the hamstrings act synergistically with the anterior cruciate ligament (ACL) to stabilize the joint and protect the ACL and other passive joint structures from injury (Draganich and Vahey 1990;Solomonow et al 1987;Yasuda and Sasaki 1987). If this is the case, then the similar antagonist values in children and adults may be attributed to the finding that the ACL is equally strong to stabilize the knee joint in both children and adults (Micheli and Coady 1997).…”
Section: Prediction Of Antagonist Momentmentioning
confidence: 98%
“…It is suggested that mechanoreceptors in the ACL are excitated and that, by means of a ligament-muscle reflex loop, the hamstring muscle is activated to maintain joint stability [32]. Co-contraction of the hamstring muscle at these angles decreases the anteriorly directed shear of the tibia [8,9,19,27,31] and thus reduces the strain on the ACL [9,19,27,33]. As the anterior displacement occurs mainly in the range of 15-45 knee flexion (where 0 is full extension) [14], it might be expected that antagonist activity would vary with knee angle with the highest antagonist activity toward full extension.…”
Section: Introductionmentioning
confidence: 99%